Traditional Institution for Forest Conservation within a Changing Community: Insight from the Case of Upland South Sumatra - Martin, Edwin; Suharjito, Didik; Darusman, Dudung; Sunito, Satyawan; Winarno, Bondan (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2016)
Referring to the studies on the success of community forestry, the proponents suggest reducing the influence of the state to the people who maintain traditional institutions in forest management. However, knowledge about the interaction of formal and informal institutions in the context of changing smallholder farmers is still not fully understood. Through a phenomenological approach assessing the differences of forest conserving institutionsâ performance across villages in Semende, South Sumatra, we analyze the process of how traditional institutions can survive or collapse. The main finding shows that traditional institutions gained support and legitimacy from governmentâs formal institutions, to enforce the rules, are able to survive until now. The key factor determining the success or failure of traditional institutions is the structure of communityâs authority; whether it is based on to inherited knowledge or not. We propose a new hypothesis for the concept of local institutions that successfully manage natural resources.